Pengaruh Perbandingan Tepung Ubi Jalar Ungu Dan Tepung Kedelai Terhadap Tingkat Kekerasan Dan Daya Terima Brownies Kukus - Tini, Fera, Rusdin Rauf, S.TP., M.P, Eni Purwani, S.Si., M.Si (2015)
Preliminary: Brownies is popular product made from wheat flour as a ratio material. wheat flour consumption gives the health problem, so it should be replaced with purple potato flour and soy flour. Objective: The purpose of the study was to determine the effect of the comparison of purple potato flour and soy flour on hardness and acceptance level of brownies. Methods: a completely randomized desing with three treatment ratios of purple potato flour and soy flour, were 80:20, 70:30, and 60:40. Results: The results showed that 60:40 treatment gave the highest of hardness. Teh acceptance test indicated that 60:40 treatments revealed the biggest acceptance level for color and over all atributes. For aroma, 80:20 treatment displayed the best acceptability. For texture, the highest acceptance level showed by 70:30 treatment. Conclusion: There is effect of purple potato flour and soy flour ratios on hardness and acceptance level of steamed brownies.